Cinema education method, is it work for group guidance and counseling? - Henny Christine Mamahit (RedWhite Press, 2020)
Group guidance and counseling services are services provided to students to develop life skills both academically and non-academically. Group guidance and counseling services are intended to develop attitudes and behaviors that bring goodness to students. The cinema education method is a method that uses film media to provide group guidance and counseling services. The cinema education method can be a means to help students understand their living conditions, the needs they want to fulfill, and can provide a perception that sees that everything or problems has a way out. Learning experiences obtained from films can help students develop ideas or solutions to help themselves.